Thiyl Radicals: From Simple Radical Additions to Asymmetric Catalysis1. Issue 50 (22nd October 2014) - Subramanian, Hariharaputhiran; Moorthy, Ramkumar; Sibi, Mukund P.
<x xml:space="preserve">Abstract</x> Thiyl radicals at play: Thiyls are significant free‐radical intermediates both in biology and chemistry. The recent search for new enantioselective methods in radical chemistry has led to the inclusion of these radicals in the toolbox of chiral organocatalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>